2015
DOI: 10.7150/thno.10804
|View full text |Cite
|
Sign up to set email alerts
|

Coating Solid Lipid Nanoparticles with Hyaluronic Acid Enhances Antitumor Activity against Melanoma Stem-like Cells

Abstract: Successful anticancer chemotherapy requires targeting tumors efficiently and further potential to eliminate cancer stem cell (CSC) subpopulations. Since CD44 is present on many types of CSCs, and it binds specially to hyaluronic acid (HA), we tested whether coating solid lipid nanoparticles with hyaluronan (HA-SLNs)would allow targeted delivery of paclitaxel (PTX) to CD44-overexpressing B16F10 melanoma cells. First, we developed a model system based on melanoma stem-like cells for experiments in vitro and in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 54 publications
(55 reference statements)
0
61
1
Order By: Relevance
“…The significant increase in particle size upon inclusion of hyaluronic acid in the aqueous phase is attributed to the hyaluronic acid coat on the particles (to be displayed in the electron microscopy pictures), in addition to the increased viscosity of the external phase of the nanoemulsion due to the presence of hyaluronic acid, leading to larger sized particles (Ibrahim et al, 2010). The increase in the negativity is also attributed to the presence of hyaluronic acid in the formulation (Shen et al, 2015).…”
Section: Measurement Of Particle Size and Zeta Potential Of Nanoemulsmentioning
confidence: 97%
“…The significant increase in particle size upon inclusion of hyaluronic acid in the aqueous phase is attributed to the hyaluronic acid coat on the particles (to be displayed in the electron microscopy pictures), in addition to the increased viscosity of the external phase of the nanoemulsion due to the presence of hyaluronic acid, leading to larger sized particles (Ibrahim et al, 2010). The increase in the negativity is also attributed to the presence of hyaluronic acid in the formulation (Shen et al, 2015).…”
Section: Measurement Of Particle Size and Zeta Potential Of Nanoemulsmentioning
confidence: 97%
“…The topical administration of Dox-loaded SLNs for melanoma could reduce systemic side effects of Dox and increase the therapeutic effectiveness. It was reported that the small particles sizes of SLNs enhance drug penetration through the stratum corneum, the outermost layer of the epidermis which is responsible for the prevention of chemicals penetration into the skin (Kelidari et al, 2015;Shen et al, 2015). This study investigated the potential of Dox-loaded SLNs for topical delivery to the melanoma cancer induced BALB/C mice animal model.…”
Section: Introductionmentioning
confidence: 97%
“…Coating of chitosan nanoparticles and PLGA nanoparticles with HA based on the same principle of physical adsorption, were reported in recent findings [30,53]. Shen et al also reported coating of HA onto PTX loaded solid lipid nanoparticles for enhanced anti tumor activity against melanoma stem like cells [54].…”
Section: Preparation Of Ha Coated Slm-npsmentioning
confidence: 90%